A core musculoskeletal anatomy syllabus for undergraduate physical therapy student education. Issue 2 (12th October 2022) - Woodley, Stephanie J.; Green, Rodney A.; Webb, Alexandra L.
Abstract: Knowledge of musculoskeletal anatomy is fundamental to physical therapy education. Although detailed anatomy syllabi have been developed for medical and other health professional students, none are available for training physical therapists. Therefore, the aim of this project was to produce a core musculoskeletal anatomy syllabus specific to physical therapy students, utilizing a modified Delphi approach. An international Delphi panel ( n  = 53) composed of anatomists and clinicians involved in physical therapy education considered a total of 2193 anatomical items arranged in four categories (musculoskeletal concepts; vertebral column; pectoral girdle and upper limb; pelvic girdle and lower limb). Using specific criteria, items were rated on the basis of whether they were considered essential knowledge for a competent physical therapy student, and were categorized as core, recommended, not recommended or not core. Of the 2193 items, 1700 (77.5%) were rated as core or recommended. For musculoskeletal concepts, 70% (233/332) of items were categorized as core/recommended. Approximately 80% of items in the other three categories were considered core/recommended—vertebral column (355/440), pectoral girdle and upper limb (513/657), and pelvic girdle and lower limb (599/764). This project presents a detailed musculoskeletal anatomy syllabus which may be used within a physical therapy curriculum. A key difference compared to published musculoskeletal anatomy syllabi for medical students is that a greater number of items are considered core/recommended (approximately 80% vs. 50%). These findings will now be considered and deliberated in accordance with the International Federation of Associations of Anatomists modified Delphi approach.